L‐Carnitine Suppresses Loss of Skeletal Muscle Mass in Patients With Liver Cirrhosis. Issue 8 (6th August 2018) - Ohara, Masatsugu; Ogawa, Koji; Suda, Goki; Kimura, Megumi; Maehara, Osamu; Shimazaki, Tomoe; Suzuki, Kazuharu; Nakamura, Akihisa; Umemura, Machiko; Izumi, Takaaki; Kawagishi, Naoki; Nakai, Masato; et al.
Abstract : L‐carnitine significantly suppressed loss of skeletal muscle mass in patients with liver cirrhosis. This significant effect was observed in patient subgroups stratified by age, sex, presence of HCC, and branched chain amino acid administration. L‐carnitine may be novel therapeutic option for sarcopenia in patients with liver cirrhosis. Abstract : Liver cirrhosis (LC) is a major cause of secondary sarcopenia. Sarcopenia makes the prognosis worse; thus, novel therapeutic options for sarcopenia in patients with LC are urgently required as they are currently limited. In this retrospective study, 158 patients with LC were screened, and 35 of those patients who were treated with L‐carnitine for more than 6 months and for whom skeletal muscle mass changes could be evaluated by computer tomography were enrolled. Of the 158 patients, 79 patients who did not receive L‐carnitine supplementation served as controls. Cases and controls were propensity score matched for age, sex, presence of hepatocellular carcinoma, and branched chain amino acid administration, and changes in skeletal muscle mass and clinical data were compared. The 35 patients who received L‐carnitine supplementation and 35 propensity score‐matched patients who did not receive carnitine supplementation comprised the final enrollment. Compared with control patients, patients who received L‐carnitine had significantly worse liver function, which is associated with rapid progress of skeletal muscle depletion. However, loss of skeletal muscle mass was significantly suppressed in patients receiving L‐carnitine, and a significant effect was observed in patient subgroups stratified by age, sex, presence of hepatocellular carcinoma, and branched chain amino acid administration. The change ratios of most laboratory data, including vitamin D and insulin‐like growth factor 1 levels, were similar in the two groups, but ammonia levels were significantly less in those receiving L‐carnitine. However, even in patients receiving L‐carnitine but not showing an ammonia decrease, loss of skeletal muscle was significantly suppressed. Conclusion: L‐carnitine suppresses loss of skeletal muscle mass and may therefore be a novel therapeutic option for sarcopenia in patients with LC. ( Hepatology Communications 2018; 00:000‐000)